SCHOOL SERVICE RESILIENCE IN INDONESIA’S ARCHIPELAGIC REGIONS: A SYSTEMATIC REVIEW OF SPATIAL ACCESSIBILITY, DISTRIBUTION OF EDUCATIONAL PERSONNEL, AND EDUCATIONAL LOGISTICS - Rudolf Kempa; Johan Pattiasina; Paul Arjanto (RADJA PUBLIKA, 2026)
Education in archipelagic regions faces structural challenges distinct from those in continental areas, particularly due to geographic fragmentation, limited transportation, the maldistribution of teachers, and vulnerabilities in infrastructure and logistics. This study aims to synthesize the literature on strategic issues in archipelagic education in Indonesia and to identify the mechanisms influencing the stability of school service delivery. The study employs a Systematic Literature Review approach following PRISMA guidelines, drawing on searches of the Scopus and Web of Science databases and official policy documents published between 2015 and 2024. A theory-informed thematic synthesis was used to identify causal pathways and intervariable relationships. The findings indicate that disparities in spatial accessibility disrupt service continuity through mobility constraints, high transportation costs, and unstable attendance. The maldistribution and low retention of teachers in disadvantaged, frontier, and remote (3T) areas exacerbate pedagogical instability, while infrastructural vulnerability and logistical delays increase the risk of operational disruptions in schools. These three dimensions form a systemic configuration that determines the resilience of educational service delivery in archipelagic regions.